Smart Building Technologies: Optimizing Energy Efficiency in Green Structures - Kumar Yegireddy, Narendra (International Journal of Psychosocial Rehabilitation, 2020)
In an era of growing environmental consciousness and a pressing need for sustainable solutions, the role of smart building technologies in optimizing energy efficiency within green structures has emerged as a critical and transformative concept. This paper delves into the intersection of smart building technologies and energy-efficient design, examining the pivotal role they play in the creation of sustainable, environmentally friendly, and economically sound buildings. By exploring the components and benefits of smart technologies, alongside the principles of energy efficiency in green construction, this paper underscores the potential for a significant reduction in energy consumption and its associated environmental impact. Through case studies and examples, it highlights real-world successes and challenges, offering insights into the practical implications of integrating smart technologies. The paper further investigates the profound environmental and economic advantages that result from these implementations, illuminating a path towards a more sustainable future. However, the road to adopting smart technologies is not without its challenges, and this paper acknowledges the limitations and constraints in the current landscape. Lastly, it looks forward to the future, exploring emerging trends and potential advancements in the field. This paper aims to inspire both industry stakeholders and policymakers to recognize the critical importance of smart building technologies in green structures and to take concerted action toward achieving more energy-efficient and eco-friendly built environments.